The effect of carbon- doped In 3 Sb 1 Te 2 ternary alloys for multibit ( MLC) phase- change memory - Kim, Hyun Soo; Kim, Yong Tae; Hwang, Ha Sub; Sung, Man Young (WILEY-V C H VERLAG GMBH, 2014)
One of the candidate materials for phase-change memory, In3Sb1Te2 (IST), shows multilevel phase transformations from amorphous to several crystalline materials of IST, intermediate phases such as InSb, SbTe and InTe. However, its volume can change abruptly in the multilevel phase transformation, and this change can lead to vacancy movement and atomic migration, which are related to failures and reliability issues. We propose the carbon-incorporated In3Sb1Te2 (IST-C) alloy, which has higher retention ability than the IST ternary alloy. Carbon atoms delay crystallization and prevent volume change during the set/reset operation. The carbon concen- tration is 12.5%, and the activation energy increases from 5.1 eV to 5.4 eV. ((c) 2014 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim)